Recent monogenic volcanism in North Central Vietnam: Implications for the regional mantle geodynamics - Le Duc, Anh; Nguyen, Hoang; Tran Thi, Huong; Shinjo, Ryuichi; Le Duc, Luong; Dang Hoai, Nhon; Pham Ngoc, Can (Vietnam Journal of Earth Sciences, 2025)
Pliocene to Pleistocene monogenic basalt volcanism in North Central Vietnam is typical of the East and Southeast Asian’ diffuse igneous province’. Exposed at Khe Sanh (4.5 Ma), Gio Linh (1.5–1.3 Ma), and Con Co Island (0.35 Ma) the Miocene activity marks the southeastern tip of the Red River Shear Zone (RRSZ) and appears to relate to the rifting of the Hue Sub-basin, triggered by the Song Ca-Rao Nay Fault system (SCRNFS). Petrological analysis of primitive samples suggests that their formation occurred via decompression melting of spinel peridotite mantle at temperatures of 1350–1400°C and pressures of 15–29 kbar. The basalts display oceanic island basalt (OIB)-type geochemical signatures, characterized by enrichment in radiogenic isotopes of Sr, Nd, Pb, and Hf. They are relatively high in TiO2 and K2O, and incompatible element concentrations. These suggest a fertile, spinel-peridotite source, influenced by in situ metasomatism and/or the presence of recycled subducted oceanic sediment melt. Given the lack of evidence for mantle plume activity beneath the region, we propose that North Central Vietnamese monogenic volcanism reflects decompression melting of a hotter-than-average (Tp ≈ 1400°C) mantle, triggered by lithospheric stretching (greater than 1.5) within the Red River and Hue Sub-basins. In the context of previous regional studies of east/southeast Asian Cenozoic volcanism, Dupal-like mantle affinity is ascribed to eastward asthenospheric flow from the Neo-Tethyan mantle following its closure due to the India-Eurasia collision in the Tertiary.